Public School Access or Stay-at-Home Partner: Factors Mitigating the Adverse Effects of the Covid-19 Pandemic on Academic Parents - Tatyana Deryugina; Olga Shurchkov; Jenna Stearns (Center for Economic Studies and ifo Institute (CESifo), 2022)
The COVID-19 pandemic created unexpected and prolonged disruptions to childcare access. Using survey evidence on time use by academic researchers before and after the pandemic, we analyze the extent to which greater access to either school-based or partner-provided childcare mitigated the severe disruptions to research observed among parents during COVID-19. We find that access to public schools offset the research time loss to a greater extent among mothers of young children relative to fathers, narrowing the emerging post-pandemic gender gap. Having a stay-at-home partner reduced the disruptions to research time equally for both genders.
Keywords: D10; J16; J44; 330; gender differences; Covid-19; academia